Motivasi Mahasiswa Universitas Fajar Dalam Memilih Fashion Sebagai Komunikasi Identitas Sosial - Bisyri, Muhammad; Rahman, Muhammad Fathur (Jurnal Ilmiah Mandala Education (JIME), 2023)
The purpose of this study is to find out how fashion as a communication tool can affect social identity and find out what are the motivations of Fajar University students in choosing fashion as a communication of their social identity. This study uses a qualitative descriptive research method, namely the data obtained such as the results of observations and interviews with informants, field notes prepared by researchers at the research location, not stated in the form of numbers. The results of the research obtained by researchers at Fajar University students that each student has various motivations and reasons in choosing the fashion they will use. When choosing Fashion someone will get an intrinsic and extrinsic drive. The fashion used is also used as a communication tool to convey the message that fashion has meaning. Fashion is considered a differentiator between one group and another, fashion is also considered to be able to clearly symbolize the social identity of an organization by looking at the special characteristics of the fashion used.